Diagnóstico de la dinámica de la Extensión Universitaria de la Universidad Técnica de Cotopaxi extensión La Maná Carrera de Ingeniería en Sistemas para determinar el fortalecimiento comunitario en el período 2010-2012. Propuesta de un plan de gestión. - Sánchez Castillo, Galo Patricio (2019)
The consideration that the University has managed a fundamental role in satisfying the social needs to preserve not only the ancient culture but the actual one, is corroborated by analyzing the historical evolution of the university extension in Latin America and Ecuador, a study that identifies the inconsistencies and limitations that the extension work has had in the theoretical and practical order. The systematization of accumulated experiences about the phenomenon extensionist on the respective study evidences the lack of scientific-research works that characterize the essence of what the university extension is, to be able to direct it in an effective and efficient way. The thesis proposes a Management Plan for the Technical University of Cotopaxi "La Maná" extension, which is focused in relating the characteristics and relationships as a system. This will demonstrate that extension is a substantive function and a university process of the university system to develop the management from there. This model is applicable to all strategic action units which are identified as extension. In addition, this work is developed for systems engineering, based on the need to recognize its importance within the university extension and the historical role that the institution has managed between the relation of the university and social environment.